Pengaruh Konsentrasi Konjak Glukomanan dan Karagenan Terhadap Karakteristik Sensoris dan Stabilitas Puding Coklat - Satika Dewi, Putri; Mualimin, Lulus; Fahmi Brillyansyah, Degita (Politeknik Negeri Ketapang, 2025)
Pudding is a dessert characterized by its chewy, soft, and easy-to-chew texture. The texture and stability of pudding are highly influenced by the use of hydrocolloids, such as konjac glucomannan and carrageenan. This study aims to determine the optimal concentration of konjac glucomannan and carrageenan to achieve the best sensory characteristics and stability. The research method used a Randomized Block Design (RBD) with konjac glucomannan concentrations of 1%, 1.5%, and 2%, and carrageenan concentrations of 0.5% and 1%. All treatments were subjected to sensory evaluation using the hedonic method for texture, color, taste, and overall preference, as well as stability testing through syneresis analysis, followed by statistical analysis using Minitab 20. The results showed that the treatment with the lowest syneresis was S2K3 (2% konjac glucomannan and 1% carrageenan), with syneresis values of 7.76% at 24 hours, 13.34% at 48 hours, and 17.62% at 72 hours. However, the sensory evaluation indicated that the S2K2 treatment was the most preferred by panelists across all parameters, with preference scores of 4.2 for texture, 4.0 for color, 4.0 for taste, and 4.4 overall. This study is expected to provide valuable insights for the development of high-quality chocolate pudding products.